Komuniciranje okoljske krize (University of Maribor Press, 2025)
Communicating the Environmental Crisis. The monograph on climate (environmental) crisis communication is the result of interdisciplinary research carried out within the ZELEN.KOM project. It responds to the growing urgency for more effective ways to address environmental challenges, as traditional approaches—focusing on dangers and catastrophic scenarios—often cause passivity or resistance. The contributions explore various aspects of environmental communication, from theoretical foundations and media discourse analysis to practical case studies in politics, tourism, education, arts, and local self-sufficiency. Special emphasis is placed on strategic message framing, positive examples, locally adapted solutions, and the role of language and storytelling as key tools for clearly and emotionally conveying complex scientific content. By integrating natural sciences, social sciences, and humanities, the monograph shows that discussing the environmental crisis is a complex process shaped by context. It marks an important step in developing this emerging research field in Slovenia and encourages further dialogue among scientists, practitioners, and the public.